ISLAMIC EDUCATION IN THE DIGITAL AGE: ASSESSING THE INTEGRATION OF CHATGPT IN IRE LEARNING - Arifa, Laily Nur (Proceeding of International Conference on Islamic Education (ICIED); Vol 8 No 1 (2023): Proceeding of International Conference on Islamic Education (ICIED), 2023)
In the rapidly evolving landscape of Artificial Intelligence (AI), ChatGPT emerges as a transformative tool with potential applications in various sectors, including education. This research delves into the critical evaluation of ChatGPT's role in Islamic Religious Education (IRE), a domain deeply rooted in spiritual, cultural, and historical contexts. Utilizing a comprehensive literature review method, assessed both the potential benefits and challenges of integrating ChatGPT into IRE. The findings underscore the tool's capabilities in enhancing student engagement, personalizing learning, and providing on-demand support. However, concerns regarding authenticity, accuracy, and cultural sensitivity were paramount. The research concludes with the emphasis on a harmonious fusion of modern AI technology and traditional Islamic teachings, advocating for a collaborative approach in the integration process. The significance of this study lies in its potential to guide the future integration of AI tools in religious education, ensuring a balance between innovation and tradition.